Abortion and Crime: Unwanted Children and Out-of-Wedlock Births - John R. Lott, Jr
Abortion may prevent the birth of ''unwanted'' children, who would have relatively small investments in human capital and a higher probability of crime. On the other hand, some research suggests that legalizing abortion increases out-of-wedlock births and single parent families, which implies the opposite impact on investments in human capital and thus crime. The question is: what is the net impact? We find evidence that legalizing abortion increased murder rates by around about 0.5 to 7 percent. Previous estimates are shown to suffer from not directly linking the cohorts who are committing crime with whether they had been born before or after abortion was legal.crime, abortion, out-of-wedlock briths, human capital